1981
DOI: 10.1002/malq.19810271304
|View full text |Cite
|
Sign up to set email alerts
|

Strict Implication in A Sequence of Extensions of S4

Abstract: Zeitcrhr. I . malh. Lugtk und Grundhf6w d . Math. Rd. 27, s. 301--212 ( 1 9 8 1 ) STRICT IMPLICATION IN A SEQUENCE OF EXTENSIONS O F S4 by DOLPH ULRICH in West Lafayette, Indiana (U.S.A.) l) Introduction Work on the problem of isolating the strict, implicational fragment of various modal logics began with [7], from which MEREDITH'S normal-form proof of completeness for the strict fragment of S 5 was extracted and included in [9]. The development of CENTZEN techniques next permitted HACKING [5] to provide axiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Moreover, no single axiom for C4 has been discovered; indeed, this is stated as an open problem in [2, page 83]. Ulrich [16] has shown that C4 is also the strict implicational fragment of each modal logic between S4 and S4.3; hence, our bases are new and shortest bases for the strict implicational fragments of these extensions of S4 as well.…”
Section: Cpp Ccpqcrcpq Ccpcqrccpqcprmentioning
confidence: 99%
“…Moreover, no single axiom for C4 has been discovered; indeed, this is stated as an open problem in [2, page 83]. Ulrich [16] has shown that C4 is also the strict implicational fragment of each modal logic between S4 and S4.3; hence, our bases are new and shortest bases for the strict implicational fragments of these extensions of S4 as well.…”
Section: Cpp Ccpqcrcpq Ccpcqrccpqcprmentioning
confidence: 99%
“…With "P" short for " p -+ r"> C 5 has as axioms tjhe siibstitut'ion instances of ( A l l P-+ P . there is an alternate proof in [12]. whose numbering is followed above-that C 5 is the st,rict implicational fragment, of S5: if -+'s are removed by replacing wffs of the form DI -+ , 8 with the corresponding expressions of the form o(i.…”
Section: "1mentioning
confidence: 99%
“…Familiarity with [12] would be helpful in 5 1 below for matters having to do with frames, models and the like, and with Ell] in the remaining sections for terminology and notation concerning matrices. But most of what is used is more or less standard and the rest easily guessed?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation